Radiotherapy effects on airway management in patients with nasopharyngeal cancer - Uzun, Davut D.; Zimmermann, Timo N.; Schmitt, Felix; Plinkert, Peter K.; Weigand, Markus A.; Debus, Jürgen; Held, Thomas; Uzun-Lang, Kristin (Cancers, 2024)
Background: At present, there is a paucity of data in the literature pertaining to the impact of radiotherapy (RT) on the success of tracheal intubation in patients with nasopharyngeal cancer (NPC). The aim of this study is to investigate the frequency of difficult tracheal intubation in patients with NPC following RT. Methods: Patients with NPC who underwent RT followed by surgery between 2012 and April 2024 at the University Hospital Heidelberg were retrospectively analyzed. Results: Twenty-three patients, predominantly males (73.9%) with a mean age of 52.9 years, were enrolled. Overall, 65.2% of the patients had an American Society of Anesthesiologists (ASA) class of III. The mean total laryngeal dose was 53.5 Gy for the main and boost plan, and the maximum total laryngeal dose was 66.61 Gy. Direct laryngoscopy was performed in 69.6% of cases, followed by 26.1% videolaryngoscopy, and 4.2% required fiberoptic intubation. In total, 47.8% of the patients had a Cormack/Lehane grade of I, followed by 43.5% with grade II and 8.7% with grade III. Overall, 87% of patients were successfully intubated on the first attempt. Conclusions: It has been demonstrated by previous studies that RT has the potential to enhance complications and difficulties encountered during airway management. While the results must be interpreted with caution, our study provides no evidence of severe impairment in advanced airway management in patients with nasopharyngeal cancer who have undergone radiotherapy.